2001
DOI: 10.2337/diabetes.50.11.2505
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C and Calcium Regulation of Adenylyl Cyclase in Isolated Rat Pancreatic Islets

Abstract: Rat islets express several isoforms of adenylyl cyclase (AC), and the regulation of AC activity in isolated islets by Ca 2؉ and protein kinase C (PKC) was investigated. At basal 2.8 mmol/l glucose, the muscarinic receptor agonist carbamylcholine chloride (CCh) evoked a concentration-dependent increase in cAMP generation with a maximum increase at least 4.5-fold above control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 73 publications
(70 reference statements)
4
31
1
Order By: Relevance
“…Although ACh is not usually recognized as a stimulator of cAMP production at low glucose concentrations by the normal islet (30 -32), a recent report suggests that such is the case (33). Using Wistar islets incubated at low glucose concentrations, we were unable to confirm this observation.…”
Section: Discussioncontrasting
confidence: 54%
“…Although ACh is not usually recognized as a stimulator of cAMP production at low glucose concentrations by the normal islet (30 -32), a recent report suggests that such is the case (33). Using Wistar islets incubated at low glucose concentrations, we were unable to confirm this observation.…”
Section: Discussioncontrasting
confidence: 54%
“…Supportive of this notion was that the glucose-induced elevation of intracellular [cAMP] in ␤-cells could be completely blocked by verapamil, which inhibits the glucose-induced influx of extracellular Ca 2ϩ to raise ␤-cell cytosolic [Ca 2ϩ ] i (17,30,31). In this regard, it has been previously shown that increased /calmodulindependent adenylate cyclase (type 3) activity, thereby leading to an increase of cAMP level in pancreatic rat islets (32). Thus, according to these observations, we propose the following pathway where glucose-or glyburide-mediated Ca 2ϩ influx increases cytosolic Ca 2ϩ , which may activate the Ca 2ϩ /calmodulin-dependent AC type 3, leading to an increase of cAMP levels that activate PKA to then mediate Erk-1/2 phosphorylation.…”
Section: S6kmentioning
confidence: 58%
“…Stimulation of this margination was lost after PKC downregulation, suggesting that PKC-α, βII or ε might be involved. In addition, cAMP concentrations in the beta cell are increased with PKC activation probably at the level of adenylyl cyclase phosphorylation and activation [158]. This suggests the existence of cross-talk between PKC signalling and the generation of cAMP, a well-known potentiator of GSIS [159].…”
Section: Modulation Of Secretory Granule Transport and Exocytosismentioning
confidence: 85%